Understanding self-consciousness - Dilek, Çağlan Çınar. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
The aim of this thesis is to understand the nature of self-consciousness by examining self and consciousness. Taking Strawson’s sense of Self as an inner mental entity as a starting point, I discuss if agency and personality should not be seen as essential features of sense of Self. After presenting Zahavi’s notion of selfhood as the prereflective experiential dimension, which is intrinsic to experience, we also see that it is the formal condition for experience. The implausibility of non-egological theories, taking experience without a subject, is shown and Zahavi’s thought that we are always pre-reflectively self-conscious is explained. Zahavi thinks that selfhood and consciousness cannot be contributed by external acts, as in Higher-Order Theories. He also has the view that the self cannot be grasped through any attempt to objectify self. Self-consciousness can be known directly from ordinary experience of the world. I examine whether Zahavi’s approach can handle unconsciousness and whether a minimal self-consciousness explain human self-consciousness, in the light of the empirical studies on blind sight and human infants. I don’t think that self-consciousness can be explained through minimal selfconsciousness, and I emphasize the effect of objectification, which creates a self, which is a different entity from the whole person. Mentality is important to achieve such an objectification, and in creating a self, which can be self-conscious. Lewis’ distinction between the machinery of self and Me is introduced, to show that a minimum sense of Self is not preliminary to full self-consciousness. I present questions this thesis leaves for further work.
Keywords: Self-consciousness (Awareness)